IMPLEMENTASI GERAKAN DESA MENGAJAR DALAM PENINGKATAN ANGKA MELEK HURUF DAN RATA-RATA LAMA SEKOLAH DI KABUPATEN BOGOR PROVINSI JAWA BARAT - David Mayor; Ajeng Ayu Syafitri (Fakultas Politik Pemerintahan IPDN, 2019)
Implementation of the Village Teaching Movement in Increasing Literacy Rates and Average School Length in Bogor Regency, , West Java Province . The Bogor District Government formed the Village Teaching Movement with the aim of increasing the accessibility of education and providing education services on non-formal channels. This study aims to find out how the implementation of the Village Teaching Movement Program in Increasing Literacy Numbers and the Average School Length in Bogor Regency, supporting and inhibiting factors, and efforts made by the government in overcoming these obstacles. This research was conceptualized based on the implementation theory proposed by George Edwards III with qualitative descriptive research methods and inductive approaches. Data obtained by using data collection techniques through interviews, observation, documentation, and triangulation. Data analysis techniques are used through data reduction, data presentation, and data verification. The results of the study show that the implementation of the Village Teaching Movement in Increasing Literacy and the Average School Length in Bogor Regency has been going well but has not been maximized. In the implementation of this program there were a number of obstacles including changes in policy, uneven socialization and low public participation. For this reason, the Bogor District Education Office seeks to improve the quality of education services and increase the establishment of junior high schools in a number of districts. Keywords: implementation, village teaching movement, education